From Terrorism to Politics, the World Armenian Congresses (1979-1985) - mustafa; sarı (Gazi Akademik Bakış)
Armenians who had used terrorism in order to gain their independence since the second half of the 19th century continued this policy during the World War I and also after the war. When they began terrorism activities again in 1970s, their aim was to draw the attention of world public to Armenian Issue. Reaching their aim, Armenians also sought to move the issue into the political arena. To this end, in 1979, 1983 and 1985, the World Armenian Congresses were organized by the Swiss James Viktor Karnusyan. The overall objective of the Congresses was to combine the Armenians scattered in different parts of the world in a political platform and by doing so make world states, at first Turkey, accept the Armenian Genocide. However, two main problems were about the congresses. The first one was that these congresses were in the shadow of the terrorism, and the other one was that the traditional Armenian Parties did not support these congresses. Despite all of them, the decisions taken at the congresses, the National Council of Armenian that was created and Armenian Constitution which was declared had historical nature. In addition, it is evident that these congresses also had a role in transporting the Armenian issue into the Political platform.